A novel citrus pectin-modified carbon paste electrochemical sensor used for copper determination in biofuel - Alves, Gustavo Murilo [UNESP]; da Silva, José Luiz [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2021)
This paper reports the construction of a citrus pectin-modified carbon paste electrode (PEC/CPE) which was applied for electrochemical sensitive detection of copper in biofuel. Considering its low cost of production and ease of handling, this novel sensor is a suitable alternative tool for ensuring the quality control of commercial bioethanol. Pectin carboxylic groups presence in the modified electrode helped increase its current response by 32% compared to the unmodified electrode. Under optimized conditions, using differential-pulse anodic stripping voltammetry, the analytical curve presented linear range from 5.0 × 10−8 to 1.0 × 10−4 mol L−1 (R = 0.999), with detection limit of 2.5 × 10−8 mol L−1, quantification limit of 8.3 × 10−8 mol L−1 and sensibility of 0.12 A mol−1 L. The PEC/CPE was successfully applied for copper determination in bioethanol fuel sample where recoveries ≥99% were obtained. The sensor presented good selectivity, reproducibility and repeatability (RSD ≤ 3.6%), with long-term stability over three months (RSD ≤ 6.3%).
Keywords: Bioethanol fuel; Carbon paste electrode; Citrus pectin; Copper; Polysaccharide; Stripping voltammetry